Men with backpacks and supplies on a muddy trail, vicinity of Dawson, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Stampeders consultation. Dawson, Y.T." Original photograph by Eric A. Hegg 2561; copied by Larss and Duclos